Community Participation in Solid Waste Management “Learn From International Best Practices” - Ngakan Ketut Acwin Dwijendra (Environmental Research Center (PPLH) of Udayana University)
In most cities of many developing countries, solid waste management is constantlygrowing to be a great issue. This is due to the rise of waste, while the city authorities has lackof finance and technical skills in collecting and disposing it effectively. The solid waste problemis nott just been responsibling of the city council but also other parties.This article reviews international cases of solid waste management programs analysesand evaluate each cases based on some selected criteria and then trs to check the possibility toapply in Denpasar City condition. The cases show that by enhancing and encouraging theinvolvement of community is one of the best way to set up a successful to sustainabile solidwaste management programs.